2011
DOI: 10.1111/j.1865-1682.2011.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Dual Infection of Peste-Des-Petits-Ruminants and Goatpox in Indigenous Goats of Central India

Abstract: Summary Peste‐des‐petits‐ruminants (PPR), bluetongue (BT) and goatpox (GP) have been well recognized as causes of significant economic losses in the small ruminant population of Asia and Africa. We describe here the occurrence of these three in an outbreak noticed in non‐descript goats from a subtropical region of central India. An investigation was carried out to confirm the aetiology of the heavy mortality in goats (74.6%, 112/150), with testing of samples from 12 surviving animals exhibiting mixed clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 18 publications
0
25
1
Order By: Relevance
“…Simultaneous infection of goats with PPRVand blue tongue virus (BTV) was reported by Mondal et al (2009). Saravanan et al (2007) reported on a natural occurrence of dual infection by PPRV and ORFV in goats, and recently, Malik et al (2011) provided evidence for mixed virus infection of goats in India involving PPRV, BTV, and goat pox virus (GPV). PPR is known to weaken the immune system of the animal by attacking the lymphatic system (Hassan et al 1994), and a recent study suggested immune cell targeting by PPRV (Pope et al 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Simultaneous infection of goats with PPRVand blue tongue virus (BTV) was reported by Mondal et al (2009). Saravanan et al (2007) reported on a natural occurrence of dual infection by PPRV and ORFV in goats, and recently, Malik et al (2011) provided evidence for mixed virus infection of goats in India involving PPRV, BTV, and goat pox virus (GPV). PPR is known to weaken the immune system of the animal by attacking the lymphatic system (Hassan et al 1994), and a recent study suggested immune cell targeting by PPRV (Pope et al 2013).…”
Section: Discussionmentioning
confidence: 94%
“…For example, when PPRV was co-administered with the bacterial pathogen Mannheimia haemolytica , enhanced pneumonia was observed [37]. In addition, in natural field settings livestock are likely to be co-infected with other viruses such as capripoxvirus and/or bluetongue virus [38], that would most likely exacerbate the onset and severity of PPR.…”
Section: Discussionmentioning
confidence: 99%
“…Goats were more susceptible to PPR and manifest severe clinical form of disease than sheep. A report from central India showed occurrence of dual infection of PPR and Goatpox in indigenous goats (Malik et al, 2011a Dhar et al, 2002;Balamurugan et al, 2012;Singh et al, 2013;Muthuchelvan et al, 2015). The expected yearly losses due to this disease may reach up to 1800 million rupees.…”
Section: Peste Des Petits Ruminants (Ppr)mentioning
confidence: 99%